Detection of SARS-CoV-2 in Human Retinal Biopsies of Deceased COVID-19 Patients - Casagrande, Maria; Fitzek, Antonia; Püschel, Klaus; Aleshcheva, Ganna; Schultheiss, Heinz-Peter; Berneking, Laura; Spitzer, Martin S.; Schultheiss, Maximilian (Ocular immunology and inflammation, 2020)
To report the presence of viral ribonucleic acid (RNA) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in human retina in deceased patients with confirmed novel coronavirus disease 2019 (COVID-19). Fourteen eyes of 14 deceased patients with confirmed COVID-19 disease were enucleated during autopsy. A sample of human retina was secured and fixed in RNAlater™. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) was performed to detect three different viral RNA sequences (RdRp-gene, E-gene and Orf1 gene) of SARS-CoV-2. In three out of 14 eyes SARS-CoV-2 viral RNA was detected in the retina of deceased COVID-19 patients. As analysis for three different sequences (RdRp-gene, E-gene and Orf1 gene) revealed positive results in RT-PCR, the existence of SARS-CoV-2 viral RNA in human retina is proven according to the standards of the World-Health-Organization. Viral RNA of SARS-CoV-2 is detectable in the retina of COVID-19 patients.